Salivary levels of total huntingtin are elevated in Huntington’s disease patients - Jody Corey-Bloom (Nature Portfolio, 2018)
Abstract Patients with Huntington’s disease (HD), an autosomal-dominant neurodegenerative disease, show substantial variability in age-of-onset, symptom severity and course of illness, warranting the need for biomarkers to anticipate and monitor these features. The HD gene encodes the disease protein huntingtin (Htt), a potentially useful biomarker for this disease. In the current study, we determined whether total Htt protein (normal plus mutant; “tHtt”) could be reliably measured in human saliva, a body fluid that is much more accessible compared to cerebral spinal fluid or even blood, and whether salivary levels of tHtt were clinically meaningful. We collected 146 saliva samples from manifest HD patients, early-premanifest individuals, late-premanifest patients, gene-negative family members and normal controls. We found that tHtt protein could be reliably and stably detected in human saliva and that tHtt levels were significantly increased in saliva from HD individuals compared to normal controls. Salivary tHtt showed no gender effects, nor were levels correlated with total protein levels in saliva. Salivary tHtt was significantly positively correlated with age, but not age-of-onset or CAG-repeat length. Importantly, salivary tHtt was significantly correlated with several clinical measures, indicating relevance to disease symptom onset and/or severity. Measurements of salivary tHtt offer significant promise as a relevant, non-invasive disease biomarker for HD, and its use could be implemented into clinical applications.